2020
DOI: 10.3390/cancers12092442
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing of α1-Adrenoceptor Antagonists: Impact in Renal Cancer

Abstract: Renal cancer ranks twelfth in incidence among cancers worldwide. Despite improving outcomes due to better therapeutic options and strategies, prognosis for those with metastatic disease remains poor. Current systemic therapeutic approaches include inhibiting pathways of angiogenesis, immune checkpoint blockade, and mTOR inhibition, but inevitably resistance develops for those with metastatic disease, and novel treatment strategies are urgently needed. Emerging molecular and epidemiological evidence suggests th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Other research revealed that human bladder cancer cells are sensitive to the apoptotic effects of terazosin and that bladder tumors exhibit reduced tissue vascularity ( Tahmatzopoulos et al, 2005 ; Martin et al, 2008 ). Recently, the above results have been confirmed by Mihalopoulos and coworkers ( Mihalopoulos et al, 2020 ).…”
Section: Quinazoline Derivatives In Urinary Bladder Cancer Therapysupporting
confidence: 67%
“…Other research revealed that human bladder cancer cells are sensitive to the apoptotic effects of terazosin and that bladder tumors exhibit reduced tissue vascularity ( Tahmatzopoulos et al, 2005 ; Martin et al, 2008 ). Recently, the above results have been confirmed by Mihalopoulos and coworkers ( Mihalopoulos et al, 2020 ).…”
Section: Quinazoline Derivatives In Urinary Bladder Cancer Therapysupporting
confidence: 67%
“…The anoikis-driven antitumor effect of α1-adrenoreceptor antagonists promises a safe-strategy in treating advanced disease—both therapeutically-resistant and castration-sensitive prostate cancer [ 143 , 256 , 257 ]. Quinazoline-based compounds developed after the pharmacological optimization of α1-adrenoceptor antagonists cause phenotypic reversion of EMT to MET and induce anoikis towards overcoming resistance to AR antiandrogens in pre-clinical models of advanced prostate cancer [ 143 , 257 , 258 , 259 ].…”
Section: The Phenotypic Landscape Of Advanced Prostate Cancermentioning
confidence: 99%
“…Existing compounds that can inhibit these clinically-validated targets may help to address this unmet need. Doxazosin (DOXA) is a quinazoline-based alpha 1-adrenergic receptor (A1AR) antagonist and is a widely-available drug used to treat benign prostate hyperplasia (BPH) and hypertension [ 19 ]. For the first time, we report the antitumor efficacy of DOXA in TNBC and explore its potential as a drug repurposing candidate.…”
Section: Introductionmentioning
confidence: 99%